The understanding by design guide to creating high-quality units - Wiggins, Grant P. (Gale Virtual Reference Library, 2011)
This book focuses on the basic concepts behind the Understanding by Design approach used by educators to create classroom curriculum that focus on students' understanding of important ideas and working backwards from there. Contains eight modules that are based on a typical workshop presentation, which can also be studied out of sequence, intended for K-16 educators.